2001
DOI: 10.1093/ajcn/73.3.574
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic index in the diet of European outpatients with type 1 diabetes: relations to glycated hemoglobin and serum lipids

Abstract: This study in European patients with type 1 diabetes showed that a lower dietary GI is related to lower Hb A(1c) concentrations, independently of fiber intake. The consumption of bread and pasta had the biggest effect on the overall dietary GI of European outpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
1
12

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(93 citation statements)
references
References 38 publications
9
71
1
12
Order By: Relevance
“…In this trial a decrease in both fasting glucose and insulin levels was achieved in the low GI group (between-and withingroup differences), as well as significant reductions in fructosamine levels (within-group difference; Jarvi et al, 1999). Generally, cross-sectional data appear to support the results of clinical trials (Wolever et al, 1999, Buyken et al, 2001. A cross-sectional study on 272 type 1 diabetic patients found a significant positive correlation between HbA 1c and dietary GI, as assessed by a 3-day food record (Wolever et al, 1999).…”
Section: Glycemic Index In Chronic Diseasementioning
confidence: 55%
“…In this trial a decrease in both fasting glucose and insulin levels was achieved in the low GI group (between-and withingroup differences), as well as significant reductions in fructosamine levels (within-group difference; Jarvi et al, 1999). Generally, cross-sectional data appear to support the results of clinical trials (Wolever et al, 1999, Buyken et al, 2001. A cross-sectional study on 272 type 1 diabetic patients found a significant positive correlation between HbA 1c and dietary GI, as assessed by a 3-day food record (Wolever et al, 1999).…”
Section: Glycemic Index In Chronic Diseasementioning
confidence: 55%
“…Among type I diabetics in Europe (Buyken et al, 2001), the mean (range) dietary GI was reported to be 57 (41-78), but regional differences existed in the correlation between dietary GI value and foods. Among subjects in southern Europe, the lowest GI quartile consumed more carbohydrate from pasta but less from white bread and potatoes than did subjects in the highest GI quartile.…”
Section: Discussionmentioning
confidence: 99%
“…So, dietary GL would be a stronger predictor of CVD risk factor than carbohydrate intake. Other researches have examined the correlations between dietary GI or GL and risk factors adjusting further confounding factors such as smoking status and alcohol consumption (Frost et al, 1999;Buyken et al, 2001;Ford & Liu, 2001;Liu et al, 2001). In the current study, after adjusting for smoking status (number of cigarettes per day) and alcohol consumption (g/week) in addition to total energy intake, dietary fiber intake, age, and exercise time, Body weight (kg) 60.3 (56.7, 63.9) 63.5 (60.1, 66.9) 65.8 (59.7, 71.8) 0.403 60.0 (56.0, 64.0) 61.9 (58.4, 65.4) 67.6 (62.3, 72.9) 0.068 BMI (kg/m 2 ) 25.2 (23.8, 26.6) 26.3 (25.1, 27.4) 26.9 (25.0, 28.8) 0.237 25.2 (23.7, 26.7) 25.5 (24.4, 26.6) 27.6 (26.0, 29.3) there were still significant correlations between dietary GI and HDL-c (P ¼ 0.011), TG (P ¼ 0.045), and IRI (P ¼ 0.021) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations